Birth preparedness and complication readiness among women attending Immuno-Prophylaxis Centre, Dr. S. C. Government Medical College, Nanded - Sonkar, Venkatramana K.; Inamdar, Ismailali F.; Gadekar, Rambhau D. (International Journal Of Community Medicine And Public Health, 2019)
Background: As signatory to United Nation’s Sustainable Development Goals, India is striving hard to achieve these goals by end of 2030, especially for goal number 3 with targets related to maternal and child health. Birth-preparedness and complication-readiness (BPCR) is a tool to promote maternal and neonatal survival. This study was conducted to assess the perception and practices of recently delivered women on BPCR with its correlates. Methods: Hospital-based cross-sectional study was conducted at Immuno-prophylaxis centre of Dr. Shankarrao Chavan Government Medical College, Nanded, Maharashtra. Women attending IPC along with their baby within two to four months of delivery for immunization of their babies during the month of March 2014 constituted study subject of this study. After obtaining informed consent, data was obtained on socio-demographic characters like age, caste, religion, education, parity, ANC registration and questions regarding birth preparedness and complications readiness in their last pregnancy. Results: Total 117 women found to be eligible as study subject. Overall BPCR index of the study population was 67.28. Proportion of women who received first antenatal check-up within first trimester, four or more antenatal checkups, saved money for childbirth and had institutional delivery were 87.18%, 86.32%, 51.28% and 100% respectively. Around 23.08% women had knowledge of at least 3 key danger signs of pregnancy while only 19.65% identified blood donor. Awareness regarding danger signs of pregnancy and arrangement for blood donor was found poor in comparison to other indicators in study subject. Conclusion: There is need of increasing awareness regarding BPCR so that perception and practices in the community increased.